Fast Inhomogeneous Plane Wave Algorithm for Homogeneous Dielectric Body of Revolution (Communications in Computational Physics, 2010)
To solve the electromagnetic scattering problem for homogeneous dielectricbodies of revolution (BOR), a fast inhomogeneous plane wave algorithm is developed.By using the Weyl identity and designing a proper integration path, the aggregationand disaggregation factors can be derived analytically. Compared with the traditionalmethod of moments (MoM), both the memory and CPU time requirements are reducedfor large-scale homogeneous dielectric BOR problems. Numerical results are given todemonstrate the validity and the efficiency of the proposed method.